Second Five Year Plan Bombay State District Poona - Government of Bombay (Government of Bombay, 1958)
The Second Five-Year Plan (1956–1961) for Poona District presents a comprehensive development strategy aimed at accelerating socio-economic progress through coordinated initiatives in agriculture, irrigation, industry, infrastructure, education, and social welfare. Covering an area of approximately 6,023 square miles with a population of nearly 1.95 million, the district is administratively divided into several subdivisions including Poona City, Haveli, Maval, Junnar, and Baramati, each characterized by diverse economic activities and development needs. Agriculture forms the backbone of the district’s economy, and the plan prioritizes increasing agricultural productivity through the distribution of improved seeds, fertilizers, and modern agricultural implements, along with land reforms such as the implementation of the Bombay Tenancy and Agricultural Lands Act, 1955, which promotes land ownership for cultivators and reduces fragmentation of holdings. Major irrigation and water resource development projects form a central component of the plan, including the Nira Project, Khadakwasla Project, Ghod Weir Scheme, and Pashpavati Bandhara, which together aim to significantly expand irrigated agricultural land and mitigate the impact of erratic rainfall. Power development initiatives, such as the establishment of the Chola Power Station and rural electrification programs, are designed to support industrial growth and improve domestic electricity supply in rural areas. Industrial development strategies emphasize the promotion of cooperative enterprises, particularly in agro-based industries such as sugar production and dairying, alongside the expansion of cottage and village industries through industrial cooperative societies. Infrastructure development focuses on improving road and transportation networks, with extensive expansion of highways and rural roads to enhance market connectivity and economic integration. The plan also highlights substantial progress in educational development, including the expansion of primary, secondary, and higher education institutions, the extension of compulsory education, and improvements in teacher training facilities. Public health initiatives include the establishment of primary health units, maternity and child welfare centers, and sanitation programs to improve healthcare accessibility and disease prevention. Additionally, social welfare measures emphasize community development through the establishment of village panchayats, cooperative movements, and programs aimed at supporting backward classes, women, and marginalized communities. Through integrated rural development programs such as the Community Development and National Extension Service initiatives, the plan seeks to promote local participation in governance and development. Overall, the Second Five-Year Plan for Poona District reflects a holistic approach to regional development, focusing on agricultural modernization, infrastructure expansion, industrial growth, and social welfare in order to build a sustainable and self-reliant economy that benefits all sections of the population.
District Poona
District Poona
Keywords: State Five Year Plan; Poona District Development; Agricultural Development Programs; Irrigation and Water Resource Projects; Cooperative Sugar Industry; Land Reforms and Tenancy Rights; Rural Electrification and Power Supply; Industrial Cooperative Societies; Road and Transport Infrastructure; Educational Expansion Initiatives; Public Health and Sanitation Services; Community Development and Panchayati Raj